Application of small angle X-ray scattering in evaluation of pore structure of superfine pulverized coal/char. (1st December 2016) - Luo, Lei; Liu, Jiaxun; Zhang, Yuchen; Zhang, Hai; Ma, Junfang; You, Yulong; Jiang, Xiumin
Highlights: A comprehensive study on the pore structures of superfine pulverized coal was conducted. Synchrotron radiation-induced small angle X-ray scattering was adopted and results were analyzed quantitatively through fractal dimensions. The effect of particle size on the pore network was concerned. The influence of different pyrolysis conditions on the changing process of pore structure was investigated. Abstract: Superfine pulverized coal as a new energy utilization method plays a significant role in alleviating pollutant emissions. It is of great interest to study the physicochemical properties of superfine pulverized coal. Pore structures acting as the channel of heat and mass transfer change with temperatures, coal ranks and pyrolysis atmospheres, etc. The investigation of the pore structure evolution during coal pyrolysis is beneficial for understanding the pyrolysis mechanisms, and guiding the practical application of superfine pulverized coal. Synchrotron radiation small angle X-ray scattering (SAXS) is a nondestructive test method with high accuracy, which can detect the open and closed pores simultaneously. Furthermore, the fractal dimensions were adopted here to characterize the coal pore structures quantitatively. The final results indicated that the fractal dimensions of pore surfaces decreased with the increase of coal ranks. Moreover, as elevating the pyrolysis temperatures, the fractal dimensions increased initially up to about 550 °C, and decreased afterwards in the lower temperature region (<800 °C). When the temperature is higher than 800 °C, there was a monotonically increasing trend of the fractal dimensions. In addition, the influence of different pyrolysis atmospheres on the pore networks was also discussed in the work. The results provide new insights into the influence of particle sizes on the evolution of pore structures during coal pyrolysis, and are helpful for developing representative molecular models of superfine pulverized coal.